Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.neuroimage.2011.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Automated hippocampal shape analysis predicts the onset of dementia in mild cognitive impairment

Abstract: The hippocampus is involved at the onset of the neuropathological pathways leading to Alzheimer’s disease (AD). Individuals with Mild Cognitive Impairment (MCI) are at increased risk of AD. Hippocampal volume has been shown to predict which MCI subjects will convert to AD. Our aim in the present study was to produce a fully automated prognostic procedure, scalable to high throughput clinical and research applications, for the prediction of MCI conversion to AD using 3D hippocampal morphology. We used an automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 67 publications
7
153
2
1
Order By: Relevance
“…6 However, these results were not in line with those in previous studies using the manual segmentation of hippocampal subfields or 3D surface mapping of the hippocampus. 5,22 As to this discrepancy, Hanseeuw et al suggested that there was a boundary difference between the studies and possible CA1 hypertrophy in aMCI. They also suggested that the reproducibility of their method would permit more consistency between studies than was possible with manual methods.…”
Section: 19mentioning
confidence: 99%
“…6 However, these results were not in line with those in previous studies using the manual segmentation of hippocampal subfields or 3D surface mapping of the hippocampus. 5,22 As to this discrepancy, Hanseeuw et al suggested that there was a boundary difference between the studies and possible CA1 hypertrophy in aMCI. They also suggested that the reproducibility of their method would permit more consistency between studies than was possible with manual methods.…”
Section: 19mentioning
confidence: 99%
“…It is also possible to use the results of previous research to limit predictive models to regions of interest 70 , although this relies on the assumption that findings from mass univariate approaches are applicable to a multi-variate analyses.…”
mentioning
confidence: 99%
“…Global hippocampal volume may not be the most accurate technique for the prediction of conversion from MCI to AD and for the classification of MCI patients. Shape analysis appears to be a more sensitive measure than volume analysis for the assessment of AD [20], [24].…”
Section: Magnetic Resonance Spectroscopy and Diffusion Tensor Imamentioning
confidence: 99%
“…In a recent study, Costafreda et al, [24] used a fully automated procedure to extract 3D hippocampal shape morphology in order to predict conversion from MCI to AD. Their predicting model had an accuracy of 80% (sensitivity 77%, and specificity 80%) which was competitive with other predictive models which used non automated measurements.…”
Section: Iib Prediction Of Conversion From MCI To Ad Studiesmentioning
confidence: 99%